Study on the potential of melaleuca cajuputi as a natural herbicide agent to suppress weed growth - Wan Masyitah Wan Daud
Weeds are diverse in their habit and habitats throughout the world. In landscape maintenance, weeds are of concern because they compete with other plants for growth factors. Modern management nowadays relies on the importance of synthetic chemicals to control weeds as unwanted plants in order to reduce the weed management cost. The use of herbicides does not represent an appropriate tool for the control of some weeds developing but leading negatively affect to the environment. Managing the landscape and natural resources are not only designing good views and environment but also upgrading and maintaining it through a good consideration to ensure the living environment. Therefore, this study aimed to explore Melaleuca cajuputi of heath forest species as potential natural herbicides agent in sustainable landscape management. To achieve this aim, we examine the allelochemical compound in plants, as well as analysis of physico-chemical properties in soil and water, and demonstrated this species as having allelopathic potential as natural herbicides, in order to determine their effectiveness towards suppressing weeds growth without degrading the environmental quality index. The result revealed that allelochemical contents only detected in plant and not in the soil properties as well as in the water bodies. Interestingly, total phenolic content was found substantially highest in the semi-mature plants stage. The overall analysis of the heath forest soil was recorded as extremely nutrient poor due to the high level of sand texture in the soil. In addition, the Water Quality Index WQI) for heath forest is 41 or Class IV which can be used for irrigation and recreation purposed only. On the other hand, to examine the efficiency of allelopathy effect, the model system was conducted over four different periods, ranging from one to four weeks and at three different concentrations: 0.5 g, 2.5 g and 5.0 g. The results revealed that the higher the concentration the better the weed suppression mechanism. The significance outcome of this research is cost-effective and eco-friendly technology of herbicides to mitigate environmental pollution in suppressing the weed growth from landscape ecological perspective. The plants used as a natural herbicides agent which can creates new habitats with balances ecosystem, improve the soil structure, enhance the visual aesthetic of landscape scenic and provide a healthy living environment to all.